POLA PENYEBARAN KONTEN HOMOSEKSUAL MELALUI MEDIA SOSIAL WATTPAD (STUDI KASUS FUJOSHI DI INDONESIA) - Wiranda Rasnika; Zafirah Quroatun 'Uyun (KINEMA: Jurnal Komunikasi dan Penyiaran, 2022)
This study aims to determine the distribution pattern of homosexual content on Wattpad based on a case study of Fujoshi in Indonesia. This research uses mixed methods with an embedded village design model, namely research that combines qualitative and quantitative data, with the main data in this study being qualitative data. The object of the research conducted by the researcher is Fujoshi in Indonesia who uses Wattpad, either as a reader, writer or writer and reader. The results obtained are the pattern of homosexual content found on the unique wattpad, namely using terms from Japanese (yaoi, uke, seme) and English (Boys Love, BL, and M-Preg). Additionally texts are produced and distributed based on favorite idol pairs. Although it is not produced every day, fanfiction is produced after receiving fan service from idol couples. After being produced, fanfiction is distributed (distributed) via Wattpad, and notification is made to consumers (readers) via notification. Consumers (fanfiction readers) of homosexual content first read because they were told by friends, searched through the internet, and because he was a KPopers. Fanfiction consumers read based on their favorite idol pairs which are then stored in the Wattpad library.